UJI DAYA TERIMA DAN NILAI GIZI COOKIES YANG DIMODIFIKASI DENGAN TEPUNG BIJI NANGKA DAN PENAMBAHAN KUBIS MERAH - Martharia Panjaitan; Albiner Siagian; Ernawati Nasution (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Jackfruit seed flour contains calcium and phosphorus. Red cabbage contains the pigment of anthocyanin. Red cabbage also contains calcium and phosphorus. If the jackfruit seed flour and red cabbage processed into foods, such as cookies, it can produce nutritious food. The purpose of this study was to determine the acceptability and nutritional value of the modified flourcookies jackfruit seeds and red cabbage. This study is an experiment of making cookies modifications from jackfruit seed flour and red cabbage with different composition ratio (15%: 5ml, 15%: 10ml, 25%: 5ml, and 25%: 10ml). Values of cookies nutrients is analyzed in the Laboratory Research Agency Medan Industrial Standards (phosphorus and calcium) and at the Center for Postharvest Research and Development Bogor Agricultural Testing Laboratory (anthocyanin) using spectrophotometry. Panelists in this research is public health student from University of North Sumatra as many as 30 people. Organoleptic test of the cookies using hedonic test methods.Acceptance test data were analyzed using Anova and Duncan. The content of nutrients (calcium, phosphorus, and anthocyanins) obtained in cookies B1K1 is 20.50 mg, 70 mg, 54.67 ppm, cookies B1K2 is 40.50 mg, 70 mg, 54.67 ppm, cookies B2K1 42.50 mg, 90 mg, 59.71 ppm, and cookies B2K2 is 50.6 mg, 90 mg, 59.75 ppm. The results showed that the organoleptic test for color, scent, taste and texture of the most preferred cookies panelists are cookies with the addition of 15% jackfruit seed flour and 5 ml of red cabbage. Based on the analysis of variance, the addition of jackfruit seed flour and red cabbage in making cookies with variations indicate a difference to the taste and texture of the cookies, but no difference in the color and scent of cookies. Suggestions from this research is that consumers can make jackfruit seed flour cookies with red cabbage essence as an alternative for healthy and cheap snacks. In addition, further research needs to be done related to the nutrient content of the other in jackfruit seed flour cookies with red cabbage essence. Keyword: Cookies, Jackfruit seed flour, red cabbage